Performance of surface-modified glass fiber/matrix under coupled humid environments and cyclic loading: An atomistic investigation - Yize Li; Soon Yee Wong; Fang Yenn Teo; Zechuan Yu; Li Sun; Renyuan Qin; Yu Zheng (Journal of Materials Research and Technology)
Fiber reinforced polymers (FRPs) tend to absorb water under long-term exposure, weakening the fiber/matrix interface and reducing mechanical properties. To improve their long-term performance, coupling agents are often used to modify the fiber surface and enhance interfacial bonding. Molecular dynamics simulations were employed to investigate the role of γ-Aminopropyltriethoxysilane (KH550) on the interfacial behavior of glass FRP composite under cyclic loading and moisture attack. Results showe that water molecules diffuse to the fiber/resin interface during fatigue, while fewer water molecules accumulate at the interface of modified glass fiber/epoxy compared to pristine glass fiber/epoxy interface by 33%. Due to the presence of hydrophobic propyl groups on the coupling agent, water molecules were resisted from the interface, and the hydrophilic hydroxyl groups in KH550 formed hydrogen bonds with water molecules, which further reduce interface damage from moisture attack. Modified glass fiber/resin interfaces exhibited 31% and 44% higher mean stress in dry and wet conditions, respectively, indicating improved bonding energy and stress resistance during fatigue simulations. These findings provide molecular-level insights into the fatigue behavior of composites in humid environments and suggest potential strategies to improve the durability of FRP composites.